Children and social exclusion : morality, prejudice, and group identity - Killen, Melanie; Rutland, Adam. (Malden, MA : Wiley-Blackwell, 2011)
'Social inclusion and exclusion are pervasive aspects of social life. Understanding when exclusion is legitimate or wrong reflects an understanding of morality. While there are times when exclusion is legitimate and fosters group functioning, there are also times when it reflects prejudicial biases and stereotypic expectations. How children weigh fairness and stereotypic expectations when making exclusion decisions is determined by their understanding of group norms, social identity, and friendships with children from other backgrounds. In our contemporary global society, few topics are as timely or pressing as exclusion. Children and Social Exclusion: Morality, Prejudice, and Group Identity delves deeply into the origins of prejudice and the emergence of morality to explain why children include some and exclude others and sheds light on the origins of stereotyping, prejudice, and social justice. By tackling these important issues from a global perspective, Children and Social Exclusion: Morality, Prejudice, and Group Identity illustrates how the concept of exclusion might be better understood in multiple cultures and reveals its implications in regions of conflict in the world'--
Includes bibliographical references (p. [197]-222) and index.
Keywords: Social integration; Children; Group identity; Identity (Psychology); Prejudices